2019
DOI: 10.1038/s41589-019-0256-z
|View full text |Cite
|
Sign up to set email alerts
|

An orange calcium-modulated bioluminescent indicator for non-invasive activity imaging

Abstract: Fluorescent indicators are widely used to visualize calcium dynamics downstream of membrane depolarization or G protein-coupled receptor activation, but are poorly suited for non-invasive imaging in mammals. Here, we report a bright calcium-modulated bioluminescent indicator named Orange CaMBI. Orange CaMBI reports calcium dynamics in single cells and, in the context of a transgenic mouse, reveals calcium oscillations in whole organs in an entirely noninvasive manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 44 publications
1
55
0
Order By: Relevance
“…One solution to improve temporal resolution is to utilize an indicator of real-time neuronal activity, such as the intracellular calcium concentration. Indeed, a calcium-dependent luciferase system, Orange CaMBI, has been reported (Oh et al, 2019). However, this system is based on Monitoring In Vivo Neural Graft Activity After SCI 31 NanoLuc-furimazine and might not be appropriate for neural grafts due to its low substrate permeability through the blood-brain barrier (Edinger et al, 1999;Su et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…One solution to improve temporal resolution is to utilize an indicator of real-time neuronal activity, such as the intracellular calcium concentration. Indeed, a calcium-dependent luciferase system, Orange CaMBI, has been reported (Oh et al, 2019). However, this system is based on Monitoring In Vivo Neural Graft Activity After SCI 31 NanoLuc-furimazine and might not be appropriate for neural grafts due to its low substrate permeability through the blood-brain barrier (Edinger et al, 1999;Su et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…One solution to improve temporal resolution is to utilize an indicator of real-time neuronal activity, such as the intracellular calcium concentration. Indeed, a calcium-dependent luciferase system, Orange CaMBI, has been reported 32 . However, this system is based on NanoLuc-furimazine and might not be appropriate for neural grafts due to its low substrate permeability through the blood-brain barrier 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…This luciferingated version of FLiCRE not only exhibits a steeper calcium dependency compared to the lightgated version of the tool, but it would also only require a non-invasive injection of NanoLuc’s substrate furimazine rather than exogenously delivered blue light through an optical fiber. Promisingly, recent studies have demonstrated the in vivo use of NanoLuc in mice (Oh et al, 2019; Su et al, 2020) and in the brain (Germain-Genevois et al, 2016) to perform bioluminescence imaging. Further engineering and optimization of this luciferin-gated FLiCRE design will be needed to enable non-invasive, molecular recording of integrated calcium activity across the brain.…”
Section: Discussionmentioning
confidence: 99%